A Comparison on the Consumption of Cultural Goods among University Students - Batvandi, Ziba; Zare, Forough (Journal of History Culture and Art Research, 2017)
The consumption of culture and cultural goods can be defined as an economic and political activity. The activity in its pure and creative form can lead to the creation of culture. Based on the new developments in the world, the role of the university and the student has changed. In these new roles, cultural element is very important. In other words, cultural consumption and lifestyle are based on the students’ cultural life and promote them to a level that can play the expected role. This study aimed to compare the amount and type of cultural goods consumption in Marine Science and Technology University students, by taking three variables into account: gender, field of study and location. These findings could lead to cultural politics and communications in such a way that provide proper distribution of cultural products and cultural knowledge of students based on personal consumption data and regard necessary measures in the field of distribution of goods between different groups of students to create more opportunities to students that they are interested in. The results suggest a significant difference among students regarding academic, cultural, and social life. This study depicts these differences.